Tooth loss and oral health-related quality of life among adult dental patients: A cross-sectional study - Nagarani Veeraboina; Dolar Doshi; Suhas Kulkarni; Shiva Kumar Patanapu; Satya Narayana Dantala; Adepu Srilatha (Wolters Kluwer Medknow Publications, 2022)
Background: Oral diseases seriously impair the quality of life (QoL) in a large number of individuals and they may affect various aspects of life. Aim: To determine the relationship between tooth loss and oral health-related quality of life (OHRQoL) among adult dental patients. Study Setting and Design: A cross-sectional study was carried out among 296 adult dental patients aged 35-44 years attending Department of Oral Medicine and Radiology of Panineeya Institute of Dental Sciences and Hospital, Hyderabad, India. Materials and Methods: Oral Health Impact Profile-14 (OHIP-14) was used to assess OHRQoL. Dentition status and periodontal status according to WHO criteria 2013 and position, number of teeth lost by Batista et al. (2014) tooth loss classification were assessed. Statistical Analysis: Mann-Whitney U test and analysis of variance were used to find prevalence and severity of OHIP-14 with tooth loss and logistic regression analysis to evaluate the association between OHIP-14 prevalence and severity based on variables. Results: Except for the subjects with history of previous dental visit, variables such as gender and reason for dental visit showed significant difference (P ≤ 0.05) with tooth loss. Males subjects, who visited dentist with a history of pain, presence of periodontal disease and tooth loss up to 12 teeth (score 3) emerged as significant predictors for OHIP-14 prevalence (OR = 6.7, OR = 1.13, OR = 3.31). Conclusion: The study strongly evidenced that number and position of tooth loss had negative impacts on OHRQoL.